PENGALAMAN PERAWAT DALAM MERAWAT PASIEN COVID-19 DENGAN KOMORBIDITAS - Wihardja, Hany; Anggraeni, Lina Dewi; Silalahi, Polmaida (Ikatan Lembaga Mahasiswa Ilmu Keperawatan Indonesia, 2022)
Introduction: In 2020 as much as 89,3% from 180 COVID-19 patients have a comorbidity. Patients with comorbidity are more at risk of being infected with COVID-19 with severe clinical manifestations. This challenge requires nurses to be more critical in treating of COVID-19 patients with comorbidity to prevent complications and mortality. This study aimed to explore the nurse’s experiences in caring for COVID-19 patients with comorbidity in private hospital in central of Jakarta. Methods: The researcher applied a phenomenological descriptive design. Data were collected using in-depth interview from 12 nurses. The participants were nurses who work in COVID-19 unit and have treated patient COVID-19 with comorbidity obtain purposive sampling. The research conducted from November 2020 to February 2021 and data were analyzed by Colaizzi’s method. Result: The study found five key themes from nurse’s experience in caring for COVID-19 patients with comorbidity that includes fear in caring for COVID-19 patients, being very exhausted, high workloads, getting lesson learn from patients and God who strengthens us. Nurses express fear when caring for COVID-19 patients because of the fast and easy transmission of COVID-19 through droplets. Nurses also feel exhausted because they have to use layered PPE while working. The theme of high workload was revealed because of the influenced on the number of nurses due to the large number of those who contracted COVID-19 while working. The source of strength theme describes nurses as being greatly strengthened by their closeness to God. Conclusion: This study explores five key themes derived from the expressions of nurses who have experience treating COVID-19 patients with comorbidities. The recommendation from the result of this study suggests that the need for personal support such as motivation and psychology support from family and coworkers so that nurses feel more confident at work. Hospitals are also expected to make approach and provide psychological support for nurses who feel mental stres such as fear or exhausted after caring for COVID-19 patients.